Bone density in haemophilia: a single institutional cross‐sectional study1. (1st August 2013) - Kempton, C. L.; Antun, A.; Antoniucci, D. M.; Carpenter, W.; Ribeiro, M.; Stein, S.; Slovensky, L.; Elon, L.
Summary Haemophilia has been associated with low bone mineral density (BMD). However, prior clinical studies of this population have neither clearly elucidated risk factors for development of low BMD nor identified who may warrant screening for osteoporosis. The aim of the study was to evaluate the relationship between BMD and haemophilic arthropathy and other demographic and clinical variables. We undertook a cross‐sectional study of BMD in adult men with haemophilia. Measures of predictor variables were collected by radiographic studies, physical examination, patient questionnaires and review of medical records. Among 88 enrolled subjects, the median age was 41 years (IQR: 20); median femoral neck BMD (n = 87) was 0.90 g cm−2 (IQR: 0.24); and median radiographic joint score was 7.5 (IQR: 18). Among subjects <50 years (n = 62), after controlling for BMI, alcohol, HIV and White race, BMD decreased as radiographic joint score increased (est. β = −0.006 mg cm−2; 95% CI −0.009, −0.003; partial R2 = 0.23). Among subjects ≥50 years (n = 26), 38% had osteoporosis (T score less than or equal to −2.5) and there was no association between BMD and arthropathy. Risk factors for low BMD in men with haemophilia <50 years include haemophilic arthropathy, low or normal BMI and HIV. Men with haemophilia over age 50 years should have routine screening for detection of osteoporosis.